Plio‐Pleistocene mammals from Mille‐Logya, Ethiopia, and the post‐Hadar faunal change. (16th July 2021) - Geraads, Denis; Reed, Denne; Barr, W. Andrew; Bobe, René; Stamos, Peter; Alemseged, Zeresenay
ABSTRACT: We describe the non‐primate mammalian fauna from the late Pliocene to earliest Pleistocene deposits of Mille‐Logya in the Lower Awash Valley, Ethiopia, dated to c. 2.9–2.4 Ma, and divided into three successive units: Gafura, Seraitu, and Uraitele. We identify 41 mammalian taxa (including rodents), the most diverse group being the Bovidae, with 17 taxa. While the Gafura assemblage still resembles those from the earlier Hadar Formation, the younger Seraitu assemblage documents a major turnover. While there is little change in the species present across this interval, the relative abundances of various taxa change dramatically, with suids being largely replaced by open‐country bovids (Alcelaphini and Antilopini). We interpret this faunal change as reflective of an environmental shift, contemporaneous with the replacement of Australopithecus afarensis by Homo in the area.